Again / Angeline Ranjethamoney R. Vijayarajoo - R. Vijayarajoo, Prof. Dr. Angeline Ranjethamoney (Universiti Teknologi MARA Cawangan Kedah, 2022)
A compilation of poems from interested 118 lecturers and academicians from UiTM and other higher learning institutions.